Jejak Dakwah Syekh H. Baihaqi di Aceh Singkil - Fadhli, Ahmad; Sarkawi, Sarkawi (Journal of Da'wah, 2024)
Da'wah is a noble task and has been explained in the Qur'an, the implementation of Da'wah itself can be carried out through various methods so that it can be achieved as expected. the scholars in carrying out da'wah have their own methods and characteristics, according to the conditions of the audience in the field and their abilities, so that when tracing the da'wah traces of the scholars, of course there are many differences. in this study the author raises the title Da'wah Traces of Sheikh H. Baihaqi in Aceh Singkil, which aims to find out how the da'wah traces and methods of implementing Da'wah carried out by Sheikh H. baihaqi. The type of research that the author uses is field research, through the History approach, where sources are obtained, through direct observation and observation, as well as other sources related to this research. from the research conducted, the author found that Sheikh H. Baihaqi had prepared himself before plunging into the wider community from various sides, including economic preparation, while the da'wah model carried out by the model of da'wah Bil lisan and da'wah bil hal, which is oriented towards the interests of the people, so as to give birth to a generation of knowledge and faith